Apoptotic induction activity of Dactyloctenium aegyptium (L.) P.B. and eleusine indica (L.) Gaerth. Extracts on human lung and cervical cancer cell lines - Hansakul P. (2014)
Dactyloctenium aegyptium (L.) P.B. (Yaa paak khwaai) and Eleusine indica (L.) Gaerth. (Yaa teen-ka) have long been used in traditional Thai medicine because of their diuretic, anti-inflamatory, and antipyretic effects. The present study examined the antiproliferative and cytotoxic effects of the hexane and butanolic extracts of these two grass species. All the grass extracts exhibited selective growth inhibition effect on human lung cancer (A549) and cervical cancer (HeLa) cells relative to normal human lung MRC-5 fibroblasts with IC50 values in a range of 202 to 845 mg/ml. Apparently, HeLa cells were more sensitive to the extracts than A549 cells. Moreover, all the extracts induced lethality in both cancer cell lines at concentrations close to 1,000 mg/ml, indicating their selective cytotoxicity effects. ELISA assay showed that only the hexane extract of D. aegyptium (L.) P.B. and E. indica (L.) Gaerth. significantly increased the apoptotic level in extract-treated A549 cells. However, DNA ladder assay detected classic DNA ladder patterns, a characteristic feature of apoptosis, in both cancer cell lines treated with all the extracts in a dose- and time-dependent manner. Taken together, these results indicate that the cytotoxic activity of the grass extracts against lung and cervical cancer cells is mediated through the induction of apoptosis.